STRENGTHENING ETHNIC AND RELIGIOUS HARMONY: IN THE PLURALIST MULTICULTURAL SOCIETY OF WEST KALIMANTAN - Moh. Haitami Salim; Reviewed By: Syamsul Kurniawan (Graduate Program of Pontianak Institute of Islamic Studies, 2012)
It is a reality that we are living in the midst of diversity of the community. Moreover, as a country with various ethnic groups, Indonesia is famous for its diversity, ranging from ethnicity, race, origin, ancestry, religion, language, custom, to the level of education, social and economic backgrounds. Just imagine this country, which now has a population of more than 200 million, is made up of hundreds and even thousands of ethnic groups, more than 525 languages and dialects spreading over approximately 17,800 large and small islands, stretching along 5,150 km between the continents of Asia and Australia, and between the Pacific Ocean and Indian Ocean at the equator.